2008
DOI: 10.1007/s10661-008-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an exotic plant surveying program in the Mojave Desert, Clark County, Nevada, USA

Abstract: Exotic species can threaten native ecosystems and reduce services that ecosystems provide to humans. Early detection of incipient populations of exotic species is a key step in containing exotics before explosive population growth and corresponding impacts occur. We report the results of the first three years of an exotic plant early detection and treatment program conducted along more than 3,000 km of transportation corridors within an area >1.5 million ha in the Mojave Desert, USA. Incipient populations of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Most eucalypt wildlings detected in this study were taller than 30-40 cm, as smaller seedlings were difficult to see (occasionally larger and already reproductive saplings, up to 5 m high, were also spotted). Other studies used similar approaches to detect alien species on roadsides (Abella et al 2009;Milton and Dean 1998;Shuster et al 2005;Wilson et al 1992). This method was chosen because it allows a fast assessment of large areas, facilitated in this case by the conspicuous nature of eucalypt wildlings (bluish colour), and because roadsides are public domain and not cultivated, which strongly increases the confidence that plants are wildlings (naturally established).…”
Section: Study Area and Wildling Density Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Most eucalypt wildlings detected in this study were taller than 30-40 cm, as smaller seedlings were difficult to see (occasionally larger and already reproductive saplings, up to 5 m high, were also spotted). Other studies used similar approaches to detect alien species on roadsides (Abella et al 2009;Milton and Dean 1998;Shuster et al 2005;Wilson et al 1992). This method was chosen because it allows a fast assessment of large areas, facilitated in this case by the conspicuous nature of eucalypt wildlings (bluish colour), and because roadsides are public domain and not cultivated, which strongly increases the confidence that plants are wildlings (naturally established).…”
Section: Study Area and Wildling Density Assessmentmentioning
confidence: 99%
“…For example roadsides are often associated with a higher availability of light, water and nutrients (Gelbard and Belnap 2003), which may favour wildling establishment (Florence 1996). The preference of invasive exotic species for disturbed sites like roadsides has been referred by several authors (Abella et al 2009;Milton and Dean 1998;Wilson et al 1992). On the other hand, the fact that many roadsides are managed using mowing equipment, may counteract the higher suitability of these places for wildling establishment.…”
Section: Survey Limitationsmentioning
confidence: 99%
“…We selected five sites based on land management records of non-native species occurrences (Abella et al 2009) to evaluate our experimental treatments. Field surveys of non-native species indicated that the populations we selected were in the early stages of establishment.…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…Brassica tournefortii is a winter annual native to the southern and eastern parts of the Mediterranean rim, where it establishes viable populations on sandy soils (Thanos et al 1991). In the Mojave Desert in southern Nevada, B. tournefortii has spread into a variety of habitats, including gypsum-derived soils (which are inhabited by numerous rare endemic plant species) (Abella et al 2009). As a winter annual, B. tournefortii seeds germinate after winter rainfall (October through April) and before many of the native annuals.…”
Section: Introductionmentioning
confidence: 99%
“…In deserts, road verges may host relatively greater native-plant biomass because of increased water collection at road edges (Starr and Mefford, 2002). Consequently, monitoring programs for exotic plants have focused on roadside surveys in the Mojave Desert (Abella et al, 2009) even though there are no published documents indicating that distributions of exotic species in the Mojave Desert are limited to roadsides.…”
Section: Introductionmentioning
confidence: 99%